Tindak Tutur Pada Tuturan Anak Dan Orang Tua di Kecamatan Samarinda Seberang Kota Samarinda: Tinjauan Pragmatik - Faridzi, Tities Savira; Elyana, Kukuh; Rijal, Syamsul (Universitas Mulawarman, 2021)
The results of the study found locutionary speech acts in the form of stating or informing something. Illocutionary speech acts consist of: (1) assertive illocutionary speech acts, including stating, complaining, proposing, and expressing opinions; (2) directive illocutionary speech acts, including ordering, requesting, and giving advice; (3) commissive illocutionary speech acts, including threatening, promising, offering, and expressing ability; (4) expressive illocutionary speech acts, including praising, accusing, apologizing, and insinuating; (5) declarative illocutionary speech acts, including justifying, forbidding, and allowing. Perlocutionary speech acts consist of: making the speech partner know, making the speech partner wait, making the speech partner answer, making the speech partner refuse, making the speech partner happy, making the speech partner work, making the speech partner assume they agree, making the speech partner afraid, making the speech partner disappointed, making the speech partner follow suggestions and activities, making the speech partner believe, encouraging the speech partner, and making the speech partner hopeful. While the politeness scale in the speech of children and parents is the scale of loss and gain, the scale of choice, the scale of indirectness, the scale of authority, and the scale of social distance.